ANALISIS PENGARUH ANCHORING BIAS DAN LOSS AVERSION DALAM PENGAMBILAN KEPUTUSAN INVESTASI DI KOTA BANDAR LAMPUNG - Rico Elhando Badri; Melian Elsa Putri (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2021)
The investment decisions made by ordinary investors are affected by the predictions and profits that the investor has. This decision making is an important aspect in dealing with several issues. The objective of this research was to find out the effect of the investor behavioral bias in finance (Anchoring Bias and Loss Aversion) in Lampung. The subject of this research was 120 active investors obtained from the securities institutions and several university investment galleries in Lampung. The method of this research was the associative method. The sampling techniques used in this research were non-probability sampling, snowball sampling, and purposive sampling. The data collecting technique used in this research was distributing questionnaires. The data analyzing technique used in this research was through multiple regression analysis and descriptive statistics. The hypothesis test used in this research was the independent t-test. The result of this research showed that the Anchoring Bias and Loss Aversion had a positive effect on the investor to make an investment decision in Bandar Lampung with a 0.00 0.05 significant level.